Analysis of the organization of international railway transport in the Republic of Kazakhstan - Stesenko, I.P. (BUKETOV BUSINESS REVIEW, 2018)
Currently, much attention is paid to the implementation of transport and innovation projects in the Republic of Kazakhstan and the world, especially such transport and logistics projects, where the Republic of Kazakhstan takes part, as the projects «Economic Belt of the Silk Road», «Western Europe - Western China», block train «Silk Wind», etc. The article analyzes the organization of international rail transport in the Republic of Kazakhstan. In addition, the article provides statistics and an assessment of trade in basic goods exported and imported through railway lines in the Republic of Kazakhstan - coal, ferrous and non-ferrous ores, crude oil and petroleum products, chemical and mineral fertilizers, grain, etc. Socio-economic prerequisites, directions and expected results of the choice of the international transport strategy of Kazakhstan with neighboring and partner countries are considered. The goals of the adoption of this strategy and the advantages for the strategy participants are evaluated. In the transport and logistics sphere, the prospects of foreign trade relations of Kazakhstan are considered. The article sums up the expediency and development of economic cooperation between the states